Socioeconomic status and early reading achievement: How working memory and cognitive flexibility mediate the relation in low‐achieving and typically developing K to first grade students. (3rd May 2022) - Barnes, Zachary T.; Boedeker, Peter; Cartwright, Kelly B.; Zhang, Bingshi
Abstract : Studies have demonstrated significant associations between executive function (EF) and reading ability. Many of these studies have evaluated this association through composite EF skills. In this study, we evaluated the indirect effects of working memory (WM) and cognitive flexibility (CF) in the relation between kindergarten socioeconomic status (SES) and first‐grade reading achievement. Through a two‐period estimation of mediating effects, we also examined these same relationships within low‐achieving (LA) and typically developing (TD) readers. For these investigations, nationally representative data from the United States were utilised from the Early Childhood Longitudinal Study, Kindergarten Class of 2010–2011. Results revealed significant EF and SES differences between TD and LA readers. Additionally, WM mediated around 11% of the association between kindergarten SES and first‐grade reading achievement while CF mediated 2.6%. The comparison of results between LA and TD readers yielded differences in mediating effects. For LA readers, 15% of the association was mediated by WM, but for TD only, 7.8% was mediated. CF mediated a small amount in both groups. Both WM and CF mediate the relation between kindergarten SES and first‐grade reading achievement. These findings are important because they provide clear evidence that EF ability may partially account for achievement gaps in reading ability from kindergarten to first grade. Highlights: What is already known about this topic There is an association between SES and reading ability. Prior studies have shown the mediating effect of composite EF skills between SES and reading ability on a variety of different age groups. What this paper adds This paper extends work on SES, EF and reading by examining the mediating effect of specific EFs on LA and TD readers in a national representative study. This paper focuses on the transition from kindergarten to first grade and finds a mediating effect of EF on reading in the earliest grades. Implications for theory, policy or practice There is a relationship between SES, EF and reading. Certain readers may rely more on WM than other students. If WM ability is compromised, it could negatively impact reading development. Implications are that supporting and improving early EF could reduce the negative impacts of SES on reading ability.